Pengaruh Model Turbulensi Aliran Terhadap Simulasi Numerik Aircurtain - Lillahulhaq, Zain; Maulana, Hasan Syafik (MEKANIKA: Jurnal Teknik Mesin, 2019)
Aircurtain commonly used in department store enterance, biocabinet, display refrigenerator even in operating room. Turbulance model, which used in air curtain simulation, involve numerical simulation result. This numerical simulation held to study various effect of turbulancy model in air curtain model. The characteristic of fluid flow in aircurtain is being shown in this paper. The 2D simulation of stady state air curtain flow is simulated using compressible fluid. k-? BSL dan Transition k-kl-? is suitable turbulance model which can be used in air curtain simulation.